ANALYZING THE EFFECT OF SOCIETY TECHNOLOGY SCIENCE APPROACH TOWARD STUDENTS SCIENTIFIC ATTITUDES FOR 5TH GRADE ELEMENTARY SCHOOL IN SCIENCE LEARNING - Agustan Syamsuddin; Irfandi Irfandi; Patta Bundu (JPPIPA (Jurnal Penelitian Pendidikan IPA), 2019)
This study aims to describe the students scientific attitude between students who followed science learning by applying the society technology science approach and conventional learning approach. This type of research included quasi-experimental research with a non-equivalent post-test only control group design. In this research paper involved 52 students of 5th grade of SD Inpres Andi Tonro in the academic year 2018/2019. Sample were chosen by using technic of simple random sampling and determination of the sample is based on the use of the formula Slovin. Data on scientific attitudes of students were collected by questionnaire. The data obtained were analyzed using descriptive and inferential statistical analysis techniques (separated variance t-test). The results of this study described that the students scientific attitude of the experimental class (using the society technology science approach) with an average score of 123.00 is classified as a very high category while the students scientific attitude of the control class (conventional learning approach) with an average score of 108.73 is classified as high category. There was significant difference in students' scientific attitudes in the group of students who learned using society technology science approach compared to the group of students who learned using the conventional learning.